Effect of solarized potting mixture on growth of black pepper (Piper nigrum L.) rooted cuttings in the nursery - A Kumar, K Kandiannan, PA Mathew, C K Thankamani, R Dinesh, S J Eapen, (Journal of Spices and Aromatic Crops, 2008)
Solarized potting mixture in combination with nutrients and biocontrol agents was evaluatedfor production of vigorous disease free rooted cuttings of black pepper. Plants raised insolarized potting mixture had better growth than plants raised in nonsolarized pottingmixture (soil, sand, and farm yard manure 2:1:1proportion). Among the various treatments,plants raised in solarized potting mixture with recommended nutrients (urea,superphosphate, potash and magnesium sulphate 4:3:2:1) showed significant increase innumber of leaves(5.3), length of roots (20cm), leaf area (177cm2), nutrient contents andbiomass (3.7g pl-1). The results indicated the superiority of solarized potting mixture forreducing the incidence of diseases besides yielding vigorous planting material. Cost ofproduction of rooted cuttings with biocontrol agents was found to be cheaper in the case ofrooted black pepper cuttings raised in solarized potting mixture. Bio control agents or biofertilizers can be mixed with solarized potting mixture.